THE INTERRELATIONSHIP OF ENGLISH LEXICON MASTERY ON PARAGRAPH COMPOSING SKILL - Ni Luh Ratna Suwari; I Ketut Wardana; Nengah Astawa (Academic Journal on English Studies (AJOES), 2021)
This study dealt with the interrelationship of English le xicon mastery on paragraphcomposing skills of the eight-grade students of Private Junior high school 1 Kerambitan. Thestudy attempted to elaborate on the effect of lexicon comprehension on students' writingability. An ex-post-facto was applied as a research design. The population of the present studyconsisted of 512 students and 64 of them were chosen as the samples using the clustersampling technique. The type of test that was used to measure the word meaningcomprehension was the cloze task and the essay test to measure the student's writing ability indescribing people and things. The data were descriptively analyzed with an inferential statisticof SPSS 26. The descriptive statistics included normality test, homogeneity test, Pearsonproduct-moment, and t-testing. The findings revealed that the more lexicon the studentsunderstand, the more successfully they can describe people or things in the text. Thecoefficient correlation was 0.502, the scale of interpretation score was between 0,40-0,60, andthe score of t-table was -1,998. It means that t-counted was high than r-table (-2,562 >-1,998).Based on the result, the study proved that the students’ lexicon mastery could affect theirdescriptive writing significantly. The study suggests the teachers apply appropriate teachingstrategies for further writing in the daily use of context.